The Influence of the Effectiveness of the Whistleblowing System, the Implementation of Good Corporate Governance, and the Role of Internal Audit on the Prevention of Fraud in the Procurement of Goods and Services at PT. BRI (Persero) Tbk - Doni Molana; M. Irsan Nasution; Renny Maisyarah (CV. Doki Course and Training, 2026)
This study aims to analyze the influence of the effectiveness of the whistleblowing system, the implementation of Good Corporate Governance (GCG), and the role of internal audit on fraud prevention in the procurement of goods and services at PT. Bank Rakyat Indonesia (Persero) Tbk. Fraud in the procurement of goods and services is one of the significant risks that can harm the company, both in terms of finance and reputation, so an effective internal control system is needed. This study uses a quantitative approach with a survey method. Primary data was obtained through the distribution of questionnaires to 100 employees related to procurement functions, internal audits, and internal control at PT. BRI (Persero) Tbk. The data analysis technique used is multiple linear regression analysis to test the influence of each independent variable on the dependent variable. The results of the study show that the effectiveness of the whistleblowing system, the implementation of Good Corporate Governance, and the role of internal audit have a positive and significant effect on the prevention of fraud in the procurement of goods and services. Simultaneously, these three variables contribute to increasing fraud prevention efforts within PT. BRI (Persero) Tbk. This research makes a practical contribution to management in strengthening the internal control system and becomes a reference for future research related to fraud prevention in the banking sector.